BROWN AND LEVINSON’S POLITENESS STRATEGY USED TO ANSWER SENSITIVE QUESTIONS BY INDONESIAN YOUNG ADULTS - Muhammad, Garindra (Journal of Innovation Research and Knowledge, 2024)
When people speak, they must carefully select words and expressions that will clearly communicate their intentions and meanings. Some topics, particularly certain types of questions, can be sensitive and make the listener feel uncomfortable. This study explores how Indonesian young adults handle such situations when they are asked sensitive questions. The research is based on Brown and Levinson's (1987) politeness theory which involves various strategies that people use to maintain social harmony in conversation. The data was collected through interviews with participants to understand how they manage these sensitive interactions. The findings reveal that the participants certain politeness strategies when responding to uncomfortable questions that are considered sensitive. These included Bald on Record, where the speaker directly addresses the issue without much concern for the listener's feelings; Positive Politeness, where the speaker tries to decrease the discomfort by showing friendliness or solidarity; and Negative Politeness, where the speaker acknowledges the imposition and tries to minimize it. The choice of strategy often depends on several social factors, including the setting of the conversation, the relationship between the people involved, and the cultural context in which the interaction takes place. For example, respondents were more likely to use Negative Politeness with older or more authoritative figures, showing respect and deference to avoid offending them. This study highlights the importance of understanding cultural and social factors when delivering sensitive questions, especially in diverse societies like Indonesia.